2012
DOI: 10.1186/1556-276x-7-189
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Co-2 × 2 nanoislands grown on Ag/Ge(111)-√3 × √3 surface studied by scanning tunneling microscopy

Abstract: We have found that Co-2 × 2 islands grown on an Ag/Ge(111)-√3 × √3 surface have hcp structure with the (11-20) orientation. The island evolution involves transformation of the unit cell shape from parallelogram into rectangular, which is accompanied by the island shape transformation from hexagonal into stripe-like. Identified are two crystallographic directions for the island growth, the pseudo-[0001] and the pseudo-[1-100]. We have observed the occurrence of a lateral shift between the topmost and the underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…For example, Morgenstern et al observed that Co nucleation and growth take place at the steps and on terraces of Ag(111) . Co growth in 3D (Volmer–Weber growth mode) forming islands was also observed on the Ag/Ge(111) surface, Au(111) surface, and HOPG surface …”
Section: Resultsmentioning
confidence: 99%
“…For example, Morgenstern et al observed that Co nucleation and growth take place at the steps and on terraces of Ag(111) . Co growth in 3D (Volmer–Weber growth mode) forming islands was also observed on the Ag/Ge(111) surface, Au(111) surface, and HOPG surface …”
Section: Resultsmentioning
confidence: 99%
“…Tsay et al demonstrated that Co grown on a Ge(111)/Ag-(√3 × √3)R30°s ubstrate does not intermix with Ge and preserves its magnetic properties [19]. This work was followed by a series of articles that addressed the various aspects of this appealing system [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…This finding was interpreted in terms of buffering properties of the intermediate Ag layer, which prevent the deposited Co atoms from germanide formation. The remarkable properties of the Co/Ag/Ge(111) surface system inspired the work in our laboratory, where, in the last several years, attention was paid to the characterization of the early stages of Co nucleation on the Ag/Ge(111) surface by means of scanning tunneling microscopy (STM) [ 12 - 14 ]. By comparing the method of the Ag/Ge(111) surface fabrication used by Tsay et al with the Ag/Ge(111) surface diagram [ 15 ], we ascribed the buffering properties to the √3 × √3 phase and explained them in the light of the existing structural models of the latter [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%